DIGITALIZATION AND SOCIAL ISOLATION: A STUDY OF POST-PANDEMIC HUMAN INTERACTION PATTERNS (Eureka Journal of Humanities and Social Research, 2025)
The COVID-19 pandemic accelerated digital transformation globally, redefining how humans connect, communicate, and maintain social relationships. While digitalization offered continuity during lockdowns, it also deepened the sense of isolation and emotional detachment. This study investigates the paradox of digital connectivity and social isolation by analyzing behavioral patterns, social media engagement, and interpersonal communication post-pandemic. Using a mixed-method approach involving online surveys (n = 1,200) and semi-structured interviews (n = 60), the research identifies how digital interactions have replaced but not fully replicated in-person connection. Results indicate increased dependence on technology for social validation, a decline in empathy-driven communication, and a rise in mental health concerns related to digital overexposure. The paper concludes by proposing strategies for balancing digital integration with authentic social engagement.
Keywords: Digitalization, Social Isolation, Human Interaction, Post-Pandemic Society, Online Behavior, Communication, Digital Well-being, Technology and Society, Sociology of Technology, Human Psychology